Prognostic and predictive impact of NOTCH1 mutations in patients with chronic lymphocytic leukemia: a tertiary single-center experience - D’Antiga, Mattia; Serafin, Andrea; Angotzi, Francesco; Cellini, Alessandro; Bevilacqua, Arianna; Leone, Giovanni; Danesin, Nicolò; Cavarretta, Chiara Adele; Piazza, Francesco; Piovan, Erich; Bonaldi, Laura; Trentin, Livio; et al. (Frontiers in Oncology, 2026)
NOTCH1 mutations (NOTCH1m) occur in 6%–12% of newly diagnosed chronic lymphocytic leukemia (CLL) patients, increasing to 15%–20% in relapsed cases. Despite their clinical relevance, the independent prognostic impact of NOTCH1m remains controversial, particularly in the era of targeted therapies, and routine testing has not been universally adopted. A retrospective, real-world study of 271 consecutive CLL patients treated at our institution was conducted between 1999 and 2023. The association of NOTCH1m with clinical outcomes and response to different treatment modalities, including chemoimmunotherapy (CIT), Bruton’s tyrosine kinase inhibitors (BTKi), and venetoclax-based regimens, was evaluated. Primary endpoints included time to first treatment (TTFT), time to second treatment (TT2T), time to next treatment (TTNT), and overall survival (OS). NOTCH1m were detected in 38/271 (14%) patients, predominantly the c.7541_7542delCT deletion (84%). After a median follow-up of 118 months, NOTCH1m patients demonstrated significantly shorter OS compared to NOTCH1 wild-type (NOTCH1wt) patients (244 vs. 293 months, HR=1.92, p=0.032), but this was not confirmed in a Cox multivariate analysis, where immunoglobulin heavy-chain variable region (IGHV) resulted as the independent prognostic variable. Importantly, 44% of Richter transformation cases harbored NOTCH1m. Among NOTCH1m patients, targeted therapies showed superior TT2T compared to CIT (NR vs. 48 months, p=0.024). No significant difference was observed in TTFT or TTNT between NOTCH1m and wild-type patients. In conclusion, NOTCH1m are associated with adverse prognosis in CLL, primarily due to increased risk of Richter transformation. Our findings support incorporating NOTCH1 mutational analysis into routine clinical practice for improved risk stratification and treatment selection.